2000
DOI: 10.1159/000053197
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Imprinted Genes and Paternal SUR1 Mutations Lead to Focal Form of Congenital Hyperinsulinism

Abstract: Persistent hyperinsulinaemic hypoglycaemia of infancy (PHHI) is a heterogeneous disorder characterized by profound hypoglycaemia due to inappropriate hypersecretion of insulin. An important diagnostic goal is to distinguish patients with a focal hyperplasia of islet cells of the pancreas (FoPHHI) from those with a diffuse abnormality of islets (DiPHHI), because the management differs significantly. The intriguing similarity between islet cell hyperplasia and tumourigenesis prompted us to investigate whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
1
25
0
2
Order By: Relevance
“…Fernandez-Marmiesse et al (10) reported five patients with paternally inherited K ATP mutations and whose post pancreatectomy pathology result was not consistent with that of focal lesion. Similar findings have been reported by other studies (1,21,27,30). There are a number of possible mechanisms as to how a heterozygous ABCC8/KCNJ11 mutation can lead to diffuse disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Fernandez-Marmiesse et al (10) reported five patients with paternally inherited K ATP mutations and whose post pancreatectomy pathology result was not consistent with that of focal lesion. Similar findings have been reported by other studies (1,21,27,30). There are a number of possible mechanisms as to how a heterozygous ABCC8/KCNJ11 mutation can lead to diffuse disease.…”
Section: Discussionsupporting
confidence: 90%
“…The resulting loss of heterozygosity (LOH) renders the b-cells biallelic for the abnormal foci, altering the K ATP channel and resulting in dysregulated insulin secretion within the focal lesion (16,17,18). The consequent imbalance in the expression of adjacent imprinted genes implicated in cell proliferation (such as CDKN1C and H19 normally expressed from the maternal allele and IGF2 paternally expressed) within the 11p15.5 region leads to focal islet cell adenomatous hyperplasia (19,20,21,22). Focal CHI is usually medically unresponsive, although diazoxide-responsive focal CHI has been recently described (23).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Surrounded by normal pancreas, these cells express a paternally derived SUR1 mutation in association with specific loss of imprinted maternal alleles of chromosome 11p, the region that includes SUR1. [13][14][15] The focal loss of maternally imprinted 11p tumor suppressor genes may be responsible for proliferation of islet cells, which are disomic for a paternally derived SUR1 mutation (SUR1 p-). 11,13 It is important to distinguish infants with diffuse SUR1 −/− and those with focal SUR1 p-lesions before surgery, because the latter are potentially curable with local resection.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The focal loss of maternally imprinted 11p tumor suppressor genes may be responsible for proliferation of islet cells, which are disomic for a paternally derived SUR1 mutation (SUR1 p-). 11,13 It is important to distinguish infants with diffuse SUR1 −/− and those with focal SUR1 p-lesions before surgery, because the latter are potentially curable with local resection. 16,17 The K ATP complex is a major pathway for coupling extracellular glucose concentration to insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In recent years, a number of genes including SUR1, Kir6.2, GCK, GLUD1, and short-chain 3-hydroxyacyl CoA dehydrogenase have been identified in infantile nesidioblastosis. [10][11][12] An association with Beckwith-Weideman syndrome has also been identified. 13,14 These genetic mutations have only rarely been identified in adult cases.…”
mentioning
confidence: 98%